The internationalization of environmental protection / Schreurs Miranda A., Elizabeth C. - Schreurs, Miranda A. [et.al] (1997)
Domestic and international linkages in environmental, politics; Chinese policy, making and global climate change, two, front diplomacy and the international community; the domestic politics of global biodiversity protection in the United Kingdom and the united states; domestic and international linkages in global environmental politics, a case- study of the Montreal; the internationalization of environmental protection in the USSR and its successor states; domestic institution and international environmental agendas in japan and Germany; zimbwe and CITES, illustrating the reciprocal.